2017
DOI: 10.5606/archrheumatol.2017.6175
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin-18 Level is Associated With Disease Activity and Interstitial Lung Disease in Patients With Dermatomyositis

Abstract: Objectives:This study aims to demonstrate the utilization of serum interleukin-18 (IL-18) level as a biomarker for disease activity and organ damage in patients with dermatomyositis (DM) or polymyositis (PM) using the Myositis Disease Activity Assessment Tool. Patients and methods: Forty-nine patients (13 males, 36 females) with idiopathic inflammatory myopathies were enrolled in the study. Patients were diagnosed with DM (n=33) or PM (n=16). Twenty age-and sex-matched healthy volunteers (9 males, 11 females) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In conclusion, serum IL-18 was strikingly elevated in DM patients, associated particularly with disease activity and ILD complications. A similar study was conducted by Yang et al [78], showing the same results for DM-DM with ILD; however, no higher serum IL-18 levels were observed in patients with PM compared with controls.…”
Section: Journal Of Immunology Researchsupporting
confidence: 78%
See 1 more Smart Citation
“…In conclusion, serum IL-18 was strikingly elevated in DM patients, associated particularly with disease activity and ILD complications. A similar study was conducted by Yang et al [78], showing the same results for DM-DM with ILD; however, no higher serum IL-18 levels were observed in patients with PM compared with controls.…”
Section: Journal Of Immunology Researchsupporting
confidence: 78%
“…(ii) Localised in inflammatory cells and capillaries in IIM patients [76]. (iii) High serum levels in DM/DM with interstitial lung disease [77,78] and PM [77].…”
Section: Journal Of Immunology Researchmentioning
confidence: 99%
“…Previous studies reported that ferritin was produced by macrophages [26] and correlated with lung function parameters and survival [27]. IL-18 was also secreted by macrophages [28], elevated in DM-ILD compared with DM without ILD [29], and correlated with the severity of pulmonary disease [30]. Together, these studies point to the importance of macrophages in the development and progression of CTD-ILD.…”
Section: Introductionmentioning
confidence: 67%
“…Several studies [4750] have found IL-18 to be elevated in the serum of DM or CADM compared to HD. IL-18 was correlated with ferritin [48] and clinical activity scores [49, 50]. Concerning interstitial lung disease (ILD), Gono et al [48] and Yang et al [49] found that IL-18 was higher in DM-associated ILD (DM-ILD) compared to DM without ILD but no difference was found between RP-ILD compared to non-RP-ILD [23, 51].…”
Section: Resultsmentioning
confidence: 99%
“…IL-18 was correlated with ferritin [48] and clinical activity scores [49, 50]. Concerning interstitial lung disease (ILD), Gono et al [48] and Yang et al [49] found that IL-18 was higher in DM-associated ILD (DM-ILD) compared to DM without ILD but no difference was found between RP-ILD compared to non-RP-ILD [23, 51]. Zou et al [52] confirmed these results in CADM neutrophils: they found an increase of IL-18 mRNA in CADM patients compared to classical DM (cDM) and HD.…”
Section: Resultsmentioning
confidence: 99%